Satyrium nepalense, a high altitude medicinal orchid of Indian Himalayan region: chemical profile and biological activities of tuber extracts - Mishra, Abhay P; Saklani, Sarla; Salehi, Bahare; Parcha, Versha; Sharifi-Rad, Mehdi; Milella, Luigi; Iriti, Marcello; Sharifi-Rad, Javad; Srivastava, Manjoosha (Cellular and Molecular Biology, 2018)
The present study investigated antioxidant and antibacterial activities of 5 different extracts and derived fractions from the S. nepalense tubers. Identification of the most active fractions, their phytochemical characterization, total phenolic and flavonoid contents, and biological activities were also evaluated. Petroleum ether, chloroform, ethyl acetate, methanol, water extracts and methanol fractions were screened for their antibacterial activity at 10, 50 and 100 mg/mL doses against ten Gram-negative and Gram-positive bacterial strains by disc diffusion method. Their total antioxidant activity was measured by DPPH and ABTS assays. Identification of the main compounds was performed by LC-MS/MS. Methanol extract exhibited the highest antioxidant (IC50= 30.79 µg/mL and 24.53 µg/mL for DPPH and ABTS, respectively) and antibacterial (MIC 71.5 to >100 µg/mL) activities in comparison with the other extracts. Levels of phenolics and flavonoids were also the highest in the same extract, i.e. 19.2 mg GAE/g and 11.20 mg QE/g, respectively. Phytochemical investigation of the active fractions of the methanol extract led to the isolation of gallic acid (19.04 mg/g) and quercetin (23.4 mg/g). Therefore, methanol extract showed an interesting potential for both antioxidant and antibacterial activities, thus deserving attention for future applications in the fields of medicinal plants and food supplements.